2014
DOI: 10.7235/hort.2014.14110
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural Therapy: Job Analysis, Performance Evaluation, and Educational Needs

Abstract: This study was conducted to provide a job analysis for, and assess the job performance of horticultural therapists, as well as examine future educational needs. To this end, a chart developed using the DACUM method was chosen as the appropriate tool for the job analysis of horticultural therapists (Study 1). Based on the chart, a survey using an evaluation form was produced to investigate the current level of job performance and future required level of horticultural therapists (Study 2). A total of 8 duties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…As a result of the job analysis conducted during this study, it was found that horticultural therapists performed six duties and 32 sub-tasks. These findings deviate from those of previous studies that examined eight duties and 45 sub-tasks (Kim et al 2014). Kim et al (2014) identified the following duties of horticultural therapists: selection of implementation institutions; diagnosis and evaluation of subjects; establishment of therapy plans; development of therapy; preparation for therapy implementation; horticultural therapy implementation; evaluation of therapy; and self-improvement of horticultural therapists.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…As a result of the job analysis conducted during this study, it was found that horticultural therapists performed six duties and 32 sub-tasks. These findings deviate from those of previous studies that examined eight duties and 45 sub-tasks (Kim et al 2014). Kim et al (2014) identified the following duties of horticultural therapists: selection of implementation institutions; diagnosis and evaluation of subjects; establishment of therapy plans; development of therapy; preparation for therapy implementation; horticultural therapy implementation; evaluation of therapy; and self-improvement of horticultural therapists.…”
Section: Resultscontrasting
confidence: 99%
“…These findings deviate from those of previous studies that examined eight duties and 45 sub-tasks (Kim et al 2014). Kim et al (2014) identified the following duties of horticultural therapists: selection of implementation institutions; diagnosis and evaluation of subjects; establishment of therapy plans; development of therapy; preparation for therapy implementation; horticultural therapy implementation; evaluation of therapy; and self-improvement of horticultural therapists. In the present study, certain tasks from previous studies were combined into broader categories to simplify the job analysis.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Step Procedure with the ability indicators for each competency as knowledge (K), skill (S) and attitude (A), where knowledge represents the definition, concept and principle required to perform the tasks, skill represents the behavioral ability that can be obtained on site when anticipated result can be produced, and attitude represents inner disposition to respond even if it does not come out as an actual behavior (Kim et al, 2014). Using this self-diagnosis questionnaire, the professor of the course faithfully explained the content of the test according to the level of university students with developmental disabilities, after which the pre-diagnosis and post-diagnosis were carried out in Week 2 after the orientation and Week 14 before the final exam in the last week, with the items rated on a 5-point scale.…”
Section: Competency-based Instructional Designmentioning
confidence: 99%